Exploring the relationship between self-efficacy, social support, academic anxiety, and academic outcomes: a meta-analysis structural equation modeling approach - Wang, Yun; Li, Dongyun; Li, Juntao; Bai, Shengnan (Frontiers in Psychology, 2025)
GoalThis study examined the correlation between self-efficacy, social support, academic anxiety, and academic outcomes. A structural equation model was constructed with academic outcomes as the dependent variable and self-efficacy as the independent variable. Social support and academic anxiety are introduced as mediating variables.MethodsA total of 59 studies published between July 2001 and February 2025 were obtained from the Web of Science, EBSCO, Taylor and Francis, Scopus, Wiley, ProQuest, and CNKI (core) databases, comprising 95 independent samples (total sample size = 49,072).Results and discussionThe results showed that self-efficacy was positively correlated with academic outcomes at a moderate to high level (r = 0.354), social support was positively correlated with academic outcomes at a moderate to low level (r = 0.245), and academic anxiety was negatively correlated with academic outcomes at a moderate to low level (r = −0.179). All correlations between variables were significant (p < 0.001). Cultural background, grade level and the types of academic outcomes measurement exerted moderating effects on some relationships: under Eastern culture, the influence of social support on academic outcomes was stronger, and the influence of self-efficacy on academic outcomes increased with grade level. The relationship between self-efficacy and academic outcomes was stronger in the objective measures group. Structural equation modeling confirmed that social support and academic anxiety mediated the relationship between self-efficacy and academic outcomes, with a total indirect effect of 14.12%. This study identified how self-efficacy, social support, and academic anxiety shape academic outcomes, providing practical insights for enhancing student learning.